Etiological Spectrum of Drug-Resistant Epilepsy - A Glimpse from North East India - Baiakmenlang Synmon; Shri Ram Sharma; Musharraf Hussain; Yasmeen Hyniewta (Indian Journal of Medical Specialities)
Introduction: Drug-resistant epilepsy (DRE) occurs in 20%–30% of all epilepsy patients. This group of patients is a clinical challenge and needs a multidisciplinary approach to achieve the etiological diagnosis and also guide their treatment protocol. Materials and Methods: A retrospective study was conducted at North Eastern Indira Gandhi Regional Institute of Health and Medical Sciences (NEIGRIHMS) in the Northeastern region of India, where patients fulfilling the definition of DRE were followed up to establish an etiological diagnosis. Clinical and drug history was taken for these patients. Electroencephalogram and neuroimaging were done in all patients. An attempt to evaluate the various etiologies causing DRE was made. Results: Thirty-three patients were included in the study after the exclusion of pseudo-resistance. Seventeen males and 16 females were included with the age range of 2–57 years. The most common clinical semiology was focal seizure with dyscognitive features seen in 16 patients. The most common etiology documented was medial temporal lobe epilepsy seen in ten patients. Conclusion: DRE is a common entity seen in this part of the country where epilepsy surgery is still out of reach. Etiology needs to be established in these groups of patients as other modes of therapy can be offered which include surgical and other interventions other than optimal drug therapy.